Efficacy and safety with ticagrelor in patients with prior myocardial infarction in the approved European label: insights from PEGASUS-TIMI 54 - Dellborg, Mikael; Bonaca, Marc P; Storey, Robert F; Steg, P Gabriel; Im, Kyung A; Cohen, Marc; Bhatt, Deepak L; Oude Ophuis, Ton; Budaj, Andrezej; Hamm, Christian; Spinar, Jindrich; Kiss, Robert G; et al. (European heart journal. Cardiovascular pharmacotherapy, 2019)
AIMS: In PEGASUS-TIMI 54, ticagrelor significantly reduced the risk of the composite of major adverse cardiovascular (CV) events by 15-16% in stable patients with a prior myocardial infarction (MI) 1-3 years earlier. We report the efficacy and safety in the subpopulation recommended for treatment in the European (EU) label, i.e. treatment with 60 mg b.i.d. initiated up to 2 years from the MI, or within 1 year after stopping previous adenosine diphosphate receptor inhibitor treatment. METHODS AND RESULTS: Of the 21 162 patients enrolled in PEGASUS-TIMI 54, 10 779 patients were included in the primary analysis for this study, randomized to ticagrelor 60 mg (n = 5388) or matching placebo (n = 5391). The cumulative proportions of patients with events at 36 months were calculated by the Kaplan-Meier (KM) method. The composite of CV death, MI, or stroke occurred less frequently in the ticagrelor group (7.9% KM rate vs. 9.6%), hazard ratio (HR) 0.80 [95% confidence interval (CI) 0.70-0.91; P = 0.001]. Ticagrelor also reduced the risk of all-cause mortality, HR 0.80 (0.67-0.96; P = 0.018). Thrombolysis in myocardial infarction major bleeding was more frequent in the ticagrelor group 2.5% vs. 1.1%; HR 2.36 (1.65-3.39; P < 0.001). The corresponding HR for fatal or intracranial bleeding was 1.17 (0.68-2.01; P = 0.58). CONCLUSION: In PEGASUS-TIMI 54, treatment with ticagrelor 60 mg as recommended in the EU label, was associated with a relative risk reduction of 20% in CV death, MI, or stroke. Thrombolysis in myocardial infarction major bleeding was increased, but fatal or intracranial bleeding was similar to placebo. There appears to be a favourable benefit-risk ratio for long-term ticagrelor 60 mg in this population. CLINICAL TRIAL REGISTRATION: http://www.clinicaltrials.gov NCT01225562.
Keywords: recidiva; Hemorrhage; Humans; ticagrelor; lidé středního věku; schvalování léčiv; Coronary artery disease; Female; rizikové faktory; značení léčiv; Aged; inhibitory agregace trombocytů; antagonisté purinergních receptorů P2Y; výsledek terapie; senioři; lidé; Post-myocardial infarction; Europe; infarkt myokardu; Drug Labeling; Ticagrelor; randomizované kontrolované studie jako téma; časové faktory; ženské pohlaví; Male; Randomized Controlled Trials as Topic; Middle Aged; Myocardial Infarction; Treatment Outcome; Dual antiplatelet treatment; Aspirin; Drug Approval; Recurrence; krvácení; Risk Assessment; mužské pohlaví; Platelet Aggregation Inhibitors; kombinovaná farmakoterapie; Purinergic P2Y Receptor Antagonists; Time Factors; hodnocení rizik; Evropa; Drug Therapy, Combination; Risk Factors